Characterization of an iPSC-based barrier model for blood-brain barrier investigations using the SBAD0201 stem cell line - Ozgür, Burak; Puris, Elena; Brachner, Andreas; Appelt-Menzel, Antje; Oerter, Sabrina; Balzer, Viktor; Holst, Mikkel Roland; Christiansen, Rasmus Folmann; Hyldig, Kathrine; Buckley, Stephen Timothy; Kristensen, Mie; Auriola, Seppo; et al. (Fluids and barriers of the CNS, 2023)
BackgroundBlood-brain barrier (BBB) models based on primary murine, bovine, and porcine brain capillary endothelial cell cultures have long been regarded as robust models with appropriate properties to examine the functional transport of small molecules. However, species differences sometimes complicate translating results from these models to human settings. During the last decade, brain capillary endothelial-like cells (BCECs) have been generated from stem cell sources to model the human BBB in vitro. The aim of the present study was to establish and characterize a human BBB model using human induced pluripotent stem cell (hiPSC)-derived BCECs from the hIPSC line SBAD0201.MethodsThe model was evaluated using transcriptomics, proteomics, immunocytochemistry, transendothelial electrical resistance (TEER) measurements, and, finally, transport assays to assess the functionality of selected transporters and receptor (GLUT-1, LAT-1, P-gp and LRP-1).ResultsThe resulting BBB model displayed an average TEER of 5474 +/- 167 ohm center dot cm2 and cell monolayer formation with claudin-5, ZO-1, and occludin expression in the tight junction zones. The cell monolayers expressed the typical BBB markers VE-cadherin, VWF, and PECAM-1. Transcriptomics and quantitative targeted absolute proteomics analyses revealed that solute carrier (SLC) transporters were found in high abundance, while the expression of efflux transporters was relatively low. Transport assays using GLUT-1, LAT-1, and LRP-1 substrates and inhibitors confirmed the functional activities of these transporters and receptors in the model. A transport assay suggested that P-gp was not functionally expressed in the model, albeit antibody staining revealed that P-gp was localized at the luminal membrane.ConclusionsIn conclusion, the novel SBAD0201-derived BBB model formed tight monolayers and was proven useful for studies investigating GLUT-1, LAT-1, and LRP-1 mediated transport across the BBB. However, the model did not express functional P-gp and thus is not suitable for the performance of drug efflux P-gp reletated studies.
Gesehen am 18.12.2024